Carbon-carbon materials and composites - Buckley, John D.; Edie, D. D. 1943- (Noyes Publications, 1993)
The major areas of carbon-carbon materials and composites are described in this comprehensive volume. It presents data and technology on the materials and structures developed for the production of carbon-carbon materials and composites. The text is composed of papers by 13 noted authors in their areas of expertise relating to the processes and production of these material systems and structures. The subject matter in the book is arranged to lead the reader through materials processing, fabrication, structural analysis, and applications of typical carbon-carbon products. The information provid.